Analytical Solution for Anomalous Diffusion of Bedload Tracers Gradually Undergoing Burial. Issue 1 (8th January 2019) - Wu, Zi; Foufoula‐Georgiou, Efi; Parker, Gary; Singh, Arvind; Fu, Xudong; Wang, Guangqian
Abstract: Accounting for the burial of tracer particles during bedload transport is an important component in the formulation of tracer dispersal in rivers. Herein we propose a modified active layer formulation, which accounts for the effect of burial and admits analytical solutions, enabling insightful exploration of the phenomenon of superdiffusion of bedload tracers at the intermediate timescale. This phenomenon has been observed in recent numerical results using the 2‐D Exner‐Based Master Equation. By assuming that tracers in the active layer can exchange with nontracer particles in the substrate layer to preserve mass, and that tracers entering the substrate layer get permanently trapped during the timescale of analysis, we are able to deduce governing equations for the tracer concentration in both layers. The active layer tracer concentration is shown to be governed by an advection‐diffusion equation with a sink term, and the increase of tracers in the substrate layer is driven by a corresponding source term. The solution for the variance of tracer population is analytically determined and can be approximated by the sum of a diffusion‐induced scaling (∝ t 1 ) and an advection‐induced scaling (∝ t 3 ) terms at the intermediate timescale, which explains the phenomenon of superdiffusion. The proposed formulation is shown to be able to capture the key characteristics of tracer transport as inferred by comparison with available results of numerical simulations. Key Points: A modified active layer formulation allows analytical treatment of tracer burial during transport Analytical solutions reproduce the advective slowdown and superdiffusion obtained by numerical simulations Intermediate timescale superdiffusion is related to an advection‐induced scaling (∝ t 3 ) caused by tracer burial